2020
DOI: 10.3389/fpubh.2020.534902
|View full text |Cite
|
Sign up to set email alerts
|

Mixture of Organophosphates Chronic Exposure and Pancreatic Dysregulations in Two Different Population Samples

Abstract: Organophosphates (OP) are a major agrochemical. The application of OP pesticides is expected to increase multifold in the coming decades. The etiology of diabetic diseases is attributed to multiple factors including OP pesticide exposure. The present study investigates pancreatic dysregulation with respect to exocrine enzymes and diabesity in groups of Pakistani and Cameroonian people exposed to a mixture of OP pesticides. Nine hundred and four OP exposed individuals were enrolled for this cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…A study conducted by Panda et al proved that OP exposure in the general population has a potential link with a higher level of insulin resistance and plasma glycated hemoglobin [ 58 ]. A clinical study reported that, in an OP-exposed group, the activity of AChE was decreased in red blood cells, whereas the concentration of lipase/amylase and insulin in plasma was increased, demonstrating direct damage to the pancreatic cells due to OP exposure [ 59 ]. In addition, after OP poisoning, the levels of malondialdehyde (MDA) and superoxide dismutase were elevated and reduced glutathione was depleted, indicating the generation of reactive oxygen species (ROS) [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Panda et al proved that OP exposure in the general population has a potential link with a higher level of insulin resistance and plasma glycated hemoglobin [ 58 ]. A clinical study reported that, in an OP-exposed group, the activity of AChE was decreased in red blood cells, whereas the concentration of lipase/amylase and insulin in plasma was increased, demonstrating direct damage to the pancreatic cells due to OP exposure [ 59 ]. In addition, after OP poisoning, the levels of malondialdehyde (MDA) and superoxide dismutase were elevated and reduced glutathione was depleted, indicating the generation of reactive oxygen species (ROS) [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the clinical study, acute organophosphate exposure was associated with hyperglycemia and then regressed after atropine treatment. From the study published by Leonel Javeres et al [ 16 ], red blood cell acetylcholinesterase activity decreased within the organophosphate exposure group, and the plasma concentrations of lipase/amylase and insulin increased in the organophosphate-exposed group. Such evidence demonstrated the effect of organophosphate on insulin resistance and direct damage to pancreatic cells in clinical investigations.…”
Section: Clinical Studies Of New-onset Diabetes Mellitus After Organophosphate Exposurementioning
confidence: 99%